2006
DOI: 10.1111/j.1365-2702.2006.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of pressure ulcers in surgical patients: a sample hospital in Turkey

Abstract: (i) Determining the incidence of pressure ulcers during surgery in Turkey; (ii) For nurses to be able to prevent surgery-related pressure ulcers, it is necessary for them to direct their care by knowing factors that have a role in the development of pressure ulcers during surgery therefore this study will be to call Turkish nurse's attention to pressure ulcers during surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
59
0
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 20 publications
7
59
0
10
Order By: Relevance
“…The population with cardiopulmonary alterations seeks health services late due to alternative clinical treatments, making surgeries the last option. The patients who developed PU in this study presented impaired skin integrity, predominantly on the third day of hospitalization, confirming the findings of another study (29) that describes onset of 98.0% of PUs in the first three days of post-operative hospitalization. In two other studies conducted with surgical (30) and critical (20) patients, the authors found out that PUs were diagnosed on the first two days of ICU hospitalization and that preventive measures should be used during and after surgical procedures.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The population with cardiopulmonary alterations seeks health services late due to alternative clinical treatments, making surgeries the last option. The patients who developed PU in this study presented impaired skin integrity, predominantly on the third day of hospitalization, confirming the findings of another study (29) that describes onset of 98.0% of PUs in the first three days of post-operative hospitalization. In two other studies conducted with surgical (30) and critical (20) patients, the authors found out that PUs were diagnosed on the first two days of ICU hospitalization and that preventive measures should be used during and after surgical procedures.…”
Section: Discussionsupporting
confidence: 79%
“…Loss of muscle mass, reduced inflammatory response, reduced albumin levels and subcutaneous tissue associated with reduced dermal-epidermal junction cause a higher risk of skin integrity rupture, as the skin does not have the proper ability to redistribute the mechanical load applied, presenting an important item for risk classification (28)(29)(30)(31) . The Braden scale, although commonly used and studied, at national and international levels, does not include age (1) .…”
Section: Discussionmentioning
confidence: 99%
“…The ruling provides a strong impetus for hospitals and researchers to better understand patients' risk factors and processes of care that may contribute to increased risk for pressure ulcers. Pressure ulcers can develop in a short time (eg, 3 days for postoperative patients) 10 ; therefore, the key to preventing ulcers is to accurately identify patients who are at risk for this complication. Patients undergoing surgical procedures who are immobile for long periods and are unable to change positions are at greater risk than are patients who are mobile.…”
mentioning
confidence: 99%
“…Sólo algunos autores refieren cifras más elevadas, con una incidencia del 55% entre pacientes con fractura de cadera en Suecia (16), o una incidencia de 54,8%, tras cualquier intervención quirúrgica, en Turquía (27). Por tanto, nuestros resultados confirman la estimación de una incidencia de UPP especialmente alta entre los pacientes sometidos a procedimientos quirúrgi-cos de cadera o rodilla (artroplastias y reparación de fracturas).…”
Section: Discussionunclassified
“…En algunos pacientes también se evidencian alteraciones en la subescala de nutrición. En este aspecto, nuestros resultados coinciden con los de los pocos investigadores que han incluido una valoración del nivel de riesgo de UPP en pacientes quirúrgicos (17, 27) y justificarían una mayor atención de los aspectos nutricionales de los pacientes previamente a la intervención quirúrgica (27). Nuestros resultados parecen indicar que la escala EMINA no discrimina bien el riesgo de UPP de forma específica en el postoperatorio de estos pacientes, ya que la puntuación obtenida mostraba el mismo nivel de riesgo, tanto en los pacientes que desarrollaron UPP como en los que no lo hicieron.…”
Section: Discussionunclassified